An epidemiological study on alcohol consumption and knowledge of its harmful effects on human health among rural adult population of adopted villages covered under field practice area of a private medical college in Udaipur, Rajasthan - Kumar, Rupesh; Luthra, Rakhi; Hathi, Maitri R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Consumption of alcohol among adults is a serious public health issue worldwide. However the knowledge of adverse effects of alcohol consumption on human health is very negligibly less in small towns and villages of India. Present study was conducted to determine the extent of alcohol intake and the knowledge of its adverse effects on human health among adult population. Methods: A cross-sectional study was carried out on randomly selected 400 rural adults from a field practice area of private medical college, Udaipur. Results: Prevalence of alcohol consumption was found to be (47.25%) with (49.36%) males and (39%) females. More than half of drinkers (55.9%) were belonging to 30-39 age group. Country liquor was preferred by (68.88%) and only (17.77%) consume English (IMFL). (56%) of alcohol consumers were drinking alcohol for more than a year. Most of the drinkers (49%) were induced by their friends, (24%) were induced/influenced by their parents. (42.25%) drinkers had knowledge of harmfulness of alcohol drinking; however the awareness per se did not have statistically significant effect for alcohol consumption. Results showed that the knowledge of excessive intake of alcohol can cause harmful effects on human health like Infertility to woman, irregular menstrual cycle, cancer were statistically significant (p<0.05) gender wise, while effects like depression, sleep disturbances, alcoholic hepatises, liver disease, malnutrition were statistically not significant (p>0.05). Conclusions: There is a need to enhance awareness on adverse effects of alcohol and at least bring down consumption level among heavy drinkers through peer group/family/community involvement.